Meta-Analysis of coagulation parameters associated with disease severity and poor prognosis of COVID-19 (2020)
Background To figure out whether abnormal coagulation parameters are associated with disease severity and poor prognosis in patients with 2019 Corona Virus Disease (COVID-19). Methods A systematic literature search was conducted using the databases PubMed, Embase, and Web of sciences until April 25, 2020. We included a total of 15 studies with 2277 patients. Platelet count (PLT), prothrombin time (PT), activated partial thromboplastin time (APTT), D-dimer (D-D) and fibrinogen (FIB) were collected and analyzed. The statistical results were expressed the effect measure by mean difference (MD) with the related 95% confidence interval (CI). Results The PLT level of severe patients was lower than that of mild patients, while the levels of PT, D-D and FIB were higher than those of mild patients (P < 0.05). The level of APTT had no statistical difference between two groups (P > 0.05). Compared to Non-ICU patients, PT of ICU patients was significantly longer (P < 0.05). In Non-survivors, PT and D-D were higher, yet PLT was lower than survivors (P < 0.05). There was no significant difference in APTT between survivors and Non-survivors (P > 0.05). The funnel plot and Egger's Regression test demonstrated that there was no publication bias. Conclusions Our data support the notion that coagulopathy could be considered as a risk factor for disease severity and mortality of COVID-19, which may help clinicians to identify the incidence of poor outcomes in COVID-19 patients.